3-Chloro-2-methylanilinium chloride monohydrate - Arbi Maroua; Khederi Lamia; Hamdi Ahmed; Rzaigui Mohamed (Acta Crystallographica Section E, 2014)
In the title hydrated salt, C7H9ClN+·Cl−·H2O, the organic cations, anions and water molecules are connected by N—H...Cl, N—H...O and O—H...Cl hydrogen bonds. These interactions lead to the formation of layers parallel to the ac plane.